STRATEGI PUBLIC RELATIONS DALAM MEMPERTAHANKANCITRA PERUSAHAAN (Studi Pada Program Pelayanan Prima PT. Tiki Jalur Nugraha Ekakurir Pada Masa Covid-19) - Muhammad Asfian Eko Hermawan (2022)
This study aims to find out what strategy the public relations of PT. JNE in maintaining the company's image through excellent service and knowing how to process the public relations strategy of PT. JNE in maintaining the company's image through excellent service by using service theory and strategic management. The method used is descriptive qualitative using primary and secondary data sources.The sampling technique was done by purposive sampling. Researchers used four stages, namely data collection, data reduction, data presentation, and data triangulation. The final result of this research shows the strategy and processes carried out by PT. Tiki Jalur Nugraha Ekakurir is using a public relations strategy with a social responsibility approach. Through the Excellent Service program activities, namely collaborating in helping the delivery of health personal protective equipment, giving donations to the government, spraying disinfectants and distributing masks in the community. From this strategic process, a responsible approach is taken to achieve positive results for the company's image. As well as the activities carried out by PT. Tiki JNE during the covid-19 period in Indonesia, received positive corporate image results from JNE users who collaborated to send donations and recipients of assistance carried out by JNE. Keywords: Corporate Image, Excellent Service, Public Relations